Identificación y evaluación de delitos ambientales en las microcuencas Rumiyacu, Mishquiyacu y Almendra, Moyobamba - Pinedo Paima, Maria Estelita (2011)
The Rumiyacu-Mishquiyacu and Almendra areas ravine they have been deforested due to an intense agricultura! and cattle activity without any technical criterion adapted by the settlers who are seated inside and about the micro basins. The exhaustion of the soil and the policy of expansion of the agricultura! frontier has generated a process of destruction of forests without precedents in this area and each year expands, Since the deforested land loses its fertility between 3-5 years, the farrner is forced to migrate to another place, thereby initiating the process of shifting agriculture. In this context, the present monograph raises the objectives: to identify the environmental crimes presented in the micro-watersheds field of study. As a result has to be: Until27 September 2010 is not any record ofreported environmental crimes, due to the lack of inforrnation on the ways to channel these complaints, as well as the little information from the institutions that have ex officio role on the protection of natural resources and administration of these conservation areas; in addition, on 27 September 2010, gave a forest fire started in the San Mateo Hill Sector; later (28 September) the Regional Natural Resources Management and Environmental Management of the Regional Government of San Martín convened an emergency meeting, with the aim of raising strategies to control the fire. For the present case, the followirig altematives appear directed to offsetting the environmental impacts generated by the social pressure of the populations seated in the Micro basins of study: Improve the environmental culture through awareness-raising and training, promote the use of productive technology appropriate to increase productivity and promote good agroforestry practices, provide technical assistance group and strengthen the capacity of management for the development of sustainable economic activities, search for the articulation of institutions involved in the administration of legal technical and environmental, implement a environmental communication network of institutional, to promote the creation of management committees of micro-watersheds, and to establish systems of compensation for ecosystem services, in addition to establishing of a single procedure for environmental complaints.